2014
DOI: 10.1016/j.jad.2014.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of Patient Health Questionnaire-9 and Edinburgh Postnatal Depression Scale for screening antepartum depression

Abstract: Objective We sought to evaluate the psychometric properties of two widely used screening scales: the Patient Health Questionnaire (PHQ-9) and Edinburgh Postnatal Depression Scale (EPDS) among pregnant Peruvian women. Methods This cross-sectional study included 1,517 women receiving prenatal care from February 2012 to March 2013. A structured interview was used to collect data using PHQ-9 and EPDS. We examined reliability, construct and concurrent validity between two scales using internal consistency indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 57 publications
2
69
0
1
Order By: Relevance
“…While some have argued for the continued use of the EPDS as a uni-dimensional scale (Reichenheim et al 2011), a growing number of studies demonstrate that a three-factor solution may be most optimal, including three related factors of depression, anhedonia, and anxiety similar to our population (Coates et al 2016; Cunningham et al 2015; Zhong et al 2014). In addition to differences in sample characteristics that may influence the structure of the EPDS, it has been suggested that timing of administration may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…While some have argued for the continued use of the EPDS as a uni-dimensional scale (Reichenheim et al 2011), a growing number of studies demonstrate that a three-factor solution may be most optimal, including three related factors of depression, anhedonia, and anxiety similar to our population (Coates et al 2016; Cunningham et al 2015; Zhong et al 2014). In addition to differences in sample characteristics that may influence the structure of the EPDS, it has been suggested that timing of administration may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Given the scarcity of studies concerning the psychometric properties of the PSQI when used among pregnant women, and given that prior studies have shown that sleep, mood, and anxiety disorders are highly prevalent among low-income pregnant women in Lima, Peru, 20,21 we sought to evaluate the psychometric properties of the Spanish-language version of the PSQI among pregnant Peruvian women during early pregnancy. We also assessed the relation of maternal early pregnancy sleep quality with measures of stress-induced sleep disturbance, and depressive and anxiety symptoms.…”
Section: Brief Summarymentioning
confidence: 99%
“…24 The Spanish-language version of the PHQ-9 was shown to work well in pregnant women with good reliability and construct validity. 20,26 In the current study, the presence of depression was defined as the PHQ-9 score ≥ 10.…”
Section: 23mentioning
confidence: 99%
“…Of note, given that prior studies have shown that sleep, mood, and anxiety disorders are highly prevalent among low-income pregnant women in Peru, 18,19 we sought to evaluate the psychometric properties, construct validity and factor structure of the Spanish-language version of FIRST questionnaire (FIRST-S) in early pregnancy (Figure 1). …”
Section: Psychometric Evaluation Of the Ford Insomnia Response To Strmentioning
confidence: 99%
“…Women were assigned to 1 of 5 depressive symptom categories based on total PHQ-9 score: (a) no depressive symptoms (0-4); (b) mild (5-9); (c) moderate (10)(11)(12)(13)(14); (d) moderately severe (15)(16)(17)(18)(19); and (e) severe (20)(21)(22)(23)(24)(25)(26)(27) depressive symptoms. For the purpose of this study, we defined presence of antepartum depression based upon total PHQ-9 score, (a) no depressive symptoms (0-9) and (b) antepartum depression (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). 25 A meta-analysis of 14 studies supports the use of a PHQ-9 score of ≥ 10 to classify subjects with major depressive disorder.…”
Section: Ford Insomnia Response To Stress Test (First)mentioning
confidence: 99%